Prediksi Ekspor Migas Indonesia Dengan Double Exponential Smoothing - Juli Christanto, Henoch; Aprius Sutresno, Stephen; Mavish, Steven; Afrianto Singgalen, Yerik; Dewi, Christine (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
In Indonesia, there are several forms of exports, one of which is oil and gas exports. The Double Exponential Smoothing method is a forecasting method that can be used to forecast oil and gas export data. This method uses two smoothing parameters, namely the average smoothing parameter alpha (α), the trend smoothing parameter beta (β). In this study, the population used is data on oil and gas exports in Indonesia. And the sample used is Indonesia's oil and gas export data from January 2020 to October 2021, we get 22 data sourced from the Central Statistics Agency (BPS). The Double Exponential Smoothing method is used because the data to be processed has a trend, both an up and a down trend and gas exports in Indonesia have an up and down pattern. The Double Exponential Smoothing method can also predict the prediction of oil and gas exports in Indonesia in the next months, November 2021 to February 2022. To process the data, the researcher used the Holt Double Exponential Smoothing method .